RELIGIOUS IDENTITY AND RELIGIOUS LEGITIMACY IN INTERNATIONAL POLITICS: THE CASE OF THE ISRAEL-UAE ABRAHAM ACCORD - Farrel Yano Tonapa; I Made Anom Wiranata; Ni Made Primar Yuliantarini; Cindy Aulia Sari (Arabic Literature Department, 2026)
This paper addresses the following question: In what ways do Israel and the UAE construct their shared religious identity and provide religious legitimacy through and for the Abraham Accords? Using interpretive-qualitative methods and guided by constructivism, this paper draws on primary and secondary sources. The findings reveal that both countries constructed their shared identity as fellow Abrahamic communities by naming their agreement after Abraham and through joint statements. Furthermore, three steps were taken to legitimize the Abraham Accords. First, both countries linked the Abraham Accords to the Abrahamic norms and teachings. Second, the UAE government cited Qur’anic verses and worked with religious authorities for domestic legitimacy. Third, the Israeli government strategically seeks international legitimacy by linking the Abraham Accords to Jewish primordial sentiment to secure broader international political support. Lastly, this paper argues that the UAE utilized the Abraham Accords to strengthen its moderate identity, whereas Israel used it to empower the global Jewish community. This study contributes to Abraham Accords discourse by emphasizing religion’s role and its intersection with international politics.